Embryogenesis Regeneration Of Porang Seeds (Amorphophallus Mulleri Blume) With Various Concentrations Of Indole Butyryc Acid (IBA) And Benzyl Amino Purine (BAP) In Vitro - Nuraisyah, Ai; Amalia, Lia; Turmuktini, Tien (Institute of Computer Science (IOCS), 2022)
The experiment was carried out in the Laboratory of the Faculty of Agriculture, University of Garut which is located in the Lab of the Faculty of Agriculture, University of Garut. This experiment was carried out from August to November 2022. The method used in this study was a factorial complete randomized design (CRD) method consisting of 2 factors, namely the concentration of auxin Growth Regulatory Substance/IBA (A) and the concentration of Cytokinin Growth Regulatory Substance/BAP (B). factor was the growth regulator auxin (A), which consisted of three concentration levels: a1 = 0 mg L-1, a2 = 0.5 mg L-1, a3 = 1 mg L-1. The second factor was cytokinin growth regulators (B) with 3 concentration levels, namely b1 = 0 mg L-1, b2 = 3 mg L-1, b3 = 6 mg L-1. This study consisted of 9 treatment combinations and each treatment consisted of 3 replications, so there were 27 experimental units. Each experimental unit consisted of 3 bottles, each bottle consisted of 1 explant, so that the total explants required were 81 seed embryo explants. The day the roots appeared showed that the treatment factor A (IBA) at level b1 showed a1 was significantly different from a2 and a3. Treatment factor A at levels b2 and b3 showed that a1 was not significantly different from a2 and a3. Treatment factor B (BAP) at level a1 showed b1 was significantly different from b2 and b3, b2 was not significantly different from b3. Treatment factor B at levels a2 and a3 showed b1, b2 and b3 were not significantly different. Based on the results of statistical analysis of the number, height shows that treatment factor A (IBA) at level b1 shows no significant difference a1, a2 and a3. Treatment factor B (BAP) on number, height, diameter, fresh weight and dry weight of shoots at level a1 showed that b1 was not significantly different from b2 and b3, b2 was not significantly different from b3. Based on the results of statistical analysis of shoot diameter, it showed that treatment factor A (IBA) at level b2 showed that a1 was significantly different from a2 and a3. The best interaction for the parameter of shoot diameter occurred in the combination of treatments a1 and b2, namely IBA 0 mg L-1 (control) and BAP 3 mg L-1 (4.22 mm)